The Battle of Bangui: The inside story of South Africa's worst military scandal since Apartheid - Kleynhans, Evert (Scientia Militaria - South African Journal of Military Studies, 2021)
The Battle of Bangui has assumed near mythical proportions within South Africa, and specifically in the South African National Defence Force (SANDF). During the battle that occurred in March 2013, a small force of crack South African troops engaged a 7 000-strong Seleka rebel force in an effort to stem their advance on Bangui – the capital of the politically unstable and resource-rich Central African Republic (CAR). Over the course of two days, the South African force fought a number of gallant actions and inflicted heavy casualties on the advancing rebel forces. However, the South Africans could not hold out indefinitely, especially against overwhelming odds and after taking some casualties during the ensuing fighting. Moreover, they soon found themselves surrounded in their makeshift base within Bangui, where they were ultimately forced to negotiate a ceasefire with the Seleka rebels. Following the ceasefire, the South African contingent returned to South Africa, and so began the process of trying to make sense of the rationale to deploy SANDF troops to CAR, and what exactly happened during the so-called ‘Battle of Bangui’. Most importantly, the country, the defence force, and the respective families, had to come to grips with the unnecessary loss of South African lives in a seemingly distant corner of Africa.